PREPARATION, CHARACTERIZATION, AND OPTIMIZATION OF MEBENDAZOLE SPHERICAL AGGLOMERATES USING MODIFIED EVAPORATIVE PRECIPITATION IN AQUEOUS SOLUTION (EPAS) - M. MODI, DHARMESHKUMAR; MODI, AKSHAT D.; PARIKH, RAJESH H.; PARIKH, JOLLY R. (International Journal of Pharmacy and Pharmaceutical Sciences, 2022)
Objective: Mebendazole is a popular benzimidazole class anthelmintic drug useful in the treatment of main infections of threadworms as well as other less common worm infections like whipworm, roundworm, and hookworm in adults and children over 2 y of age. It is poorly soluble in water resulting in poor absorption from the intestinal tract leading to a decrease in bioavailability. Moreover, Mebendazole has poor flowability due to the needle-shaped crystals. This work was carried out with the aim of increasing the flowability and solubility of Mebendazole. Methods: A 32 full factorial design was used to investigate the effect of the concentration of Mebendazole and the quantity of water as an external phase using evaporative precipitation into an aqueous solution. The prepared agglomerates were characterized for particle size distribution, shape, Hausner ratio, Carr’s index and % dissolved in 60 min (C60). Results: The prepared agglomerates were found to be monodispersed. They also showed a decrease in the Hausner ration and Carr’s index, indicating improved flowability. Increase in C60 indicated that the agglomerates were found to have increased water solubility. Conclusion: Scanning Electron Microscopy showed that the agglomerates were spherical in shape. Fourier Transformed Infra-Red studies showed no chemical change in the prepared spherical agglomerates. Differential Scanning Calorimetry and X-ray diffraction studies showed an increase in amorphous characteristics of prepared spherical agglomerates. This method may be used for drugs with similar characteristics as Mebendazole.